Variations in moisture content affect the shrinkage of Gigantochloa scortechinii and Bambusa vulgaris at different heights of the bamboo culm - Anokye, Rogerson; Kalong, Regina Maria; Bakar, Edi Suhaimi; Ratnasingam, Jegathewaran; Jawaid, Mohammad; Awang, Khairul (North Carolina State University, 2014)
Malaysia has more than 50 species of bamboo, but few that are utilized commercially. In this study, the physical properties of two of the most popular bamboo species in Malaysia, Gigantochloa scortechinii and Bambusa vulgaris, were evaluated. Moisture content (MC) and shrinkage variation at different height sections at both nodal and internodal categories of the bamboo culm were investigated. A comparison between the height sections and between the nodal and internodal categories, as well as between the species, was carried out. Results indicated a trend of decreasing MC along the culm from base to top, though the difference was not statistically significant. It was also observed that radial shrinkage was slightly greater than tangential shrinkage and was much greater than shrinkage in the longitudinal direction. Nodes appeared to have lower MC and a higher percentage of shrinkage compared to internodes. The shrinkage pattern of the two species of bamboo showed a small radial-to-tangential ratio of 1.15:1, which may have contributed to the dimensional stability of bamboo.